Influence of Photoperiod, Light Intensity and Their Interaction on Health Indices of Modern Broilers Grown to Heavy Weights - Olanrewaju , H.A.; Miller, W.W.; Maslin, W.R.; Collier, S.D.; Purswell, J.L.; Branton, S.L. (International Journal of Poultry Science, 2015)
The effects of photoperiod, light-intensity and their interaction on health indices of broiler chickens grown to heavy weights under environmentally controlled conditions were evaluated in 2 trials. In each trial, 540 Ross × Ross 708 chicks were randomly distributed into 9 environmentally controlled chambers (30 male and 30 female chicks/chamber) at d of hatch, provided with 23L:1D with 20 lx of intensity from placement to 7 d and then subjected to the following treatments. The treatments consisted of 3 photoperiod (long/continuous (23L:1D) from d 8 to d 56; regular/intermittent (2L:2D) and short/non-intermittent (8L:16D) from d 8 to d 48 and 23L:1D from d 49 to d 56, respectively) and exposure to 3 light intensities (10, 5.0 and 0.5 lx) from d 8 through d 56 at 50% RH. All birds were fed the same nutritionally complete diet. Feed and water were provided ad libitum. Ocular health and general health assessments were performed on d 42 and 49, respectively, while foot pad score was evaluated on d 56 of age. There were only significant (P < 0.05) effects of photoperiod on live BW and eye weight, but no differences on ocular weight relative to BW. Food pad lesions quality was significantly decreased with decreasing in photoperiod. There were no differences among treatments on ocular assessments, gait scoring test or tonic immobility responses, suggesting that these treatments did not compromise welfare of the birds. These results indicate that long/continuous and regular/intermittent photoperiods equally improved broiler performance compared with short/non-intermittent photoperiod and no significant effect of light intensity treatments was observed in this study.